OPTIMALISASI PENDEKATAN PENDIDIKAN AGAMA ISLAM DALAM PENDIDIKAN KARAKTER RELIGIUS - Haris Ibrahim; Yunus Yunus (JIEBAR : Journal of Islamic Education: Basic and Applied Research, 2021)
This study describes the optimization of Islamic religious education in realizing the religious character of students. This research is a qualitative research that uses a sociological approach. Sources of data, namely primary data sourced from school principals and their representatives, PAI teachers, students. Meanwhile, secondary data were taken from documents related to the research. The instrument used in collecting data is the researcher himself who functions to determine and select informants as data sources, analyze data, interpret data, and the instruments in collecting data are observation, interviews, and documentation. The need for the creativity of PAI teachers so that learning continues to run well, smoothly, and fun. Therefore, one of the mandatory innovations in PAI learning during the COVID-19 pandemic is online or online learning. Optimizing the realization of religious character is carried out by several approaches, namely: experience, emotional habituation, rational, functional exemplary. However, families and teachers are expected to work together to be more active in supervising and motivating students to get used to doing behavior that is characterized by personality.